Evaluación técnico-financiera a nivel de laboratorio de la utilización del poliacrilato de sodio como extendedor de bentonita en fluidos de perforación base agua (2016)
This work describes the characteristics and properties of Bentonite, Benex, KemDrill A-2051, KemDrill A-2053 and Sodium Polyacrylate extenders in order to evaluate the technical and financial viability of this front to the last three. Previously, the two were discriminated in order to know their properties and behavior as a result of the expansion of Bentonite in a water-based drilling fluid and so on by the Sodium Polyacrylate. Three drilling fluids were made with each of the four Bentonite extenders previously, subsequently rheology, filtration and chemical tests were performed for each of them, from which the drilling fluid was chosen with the best concentration Behavior for each extender. From the results obtained and analyzed in the laboratory tests the extensions of Bentonite Benex and KemDrill A-2053 were ruled out, while the results were chosen thanks to the results acquired in all the tests, were KemDrill A-2051 and Sodium Polyacrylate.